Partisisipasi masyarakat Suak Nie dalam Pelestarian Hutan Kota di Gampong Suak Nie Aceh Barat - Ulfa Maulia; Yansuril Amin; Cut Apriliana Maulidar; Wirdatul Ahya; Nadiatul Asra; Rifa Susila; Sopar Sinambela (Indo Publishing, 2026)
This study examines the participation of the Suak Nie village community in the conservation of the Suak Nie City Forest Park in West Aceh. A qualitative approach with a single case study was applied; data were collected through observation, in-depth interviews (Keuchik, youth leader, residents), and focus group discussions (FGDs), then analyzed thematically using source triangulation. Results indicate a low-moderate level of participation, with the dominant forms being fire prevention, water channel cleaning, and fencing to control livestock access. There are differences in perceptions between actors: the Keuchik reported active participation and cooperation with the government, while the youth leader assessed that the community was less participatory due to economic preoccupations and an attitude that the responsibility rests solely with the local government. The threat of peatland fires is a major issue, while illegal logging is limited due to the dominance of fern vegetation. Conclusion: participation is hampered by economic priorities and a lack of coordination. Recommendations: training and outreach programs tailored to agricultural schedules, the establishment of community patrols with simple incentives, and regular reforestation campaigns to raise environmental awareness.